1999
DOI: 10.1034/j.1600-0420.1999.770105.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low alcohol consumption on visual evoked potential, visual field and visual contrast sensitivity

Abstract: ABSTRACT.Purpose: We studied changes in the vision of 16 people after consumption of a small quantity of alcohol, at a blood alcohol level (BAL) of 0.57 g/kg. Methods: We studied visual contrast sensitivity (VCS) using Vistech VCTS 6500, visual evoked potential (VEP) by checked pattern stimulations and the peripheral visual field (PVF) with a perimetric automatic Humphrey. We first carried out the tests on sober people and then on individuals with a BAL of 0.57 g/kg. Results: Alcohol consumption caused no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 8 publications
1
17
0
2
Order By: Relevance
“…On the other hand, some studies found no change in contrast sensitivity with the use of static stimuli at 0.08% BAC (12,23). This difference from the results of the above studies may be due to differences in the methodological aspects (luminance, and stimuli alcohol concentrations) used in each study.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, some studies found no change in contrast sensitivity with the use of static stimuli at 0.08% BAC (12,23). This difference from the results of the above studies may be due to differences in the methodological aspects (luminance, and stimuli alcohol concentrations) used in each study.…”
Section: Discussionmentioning
confidence: 94%
“…This close association between positive blood alcohol test and seriousness of accidents is probably due to alcoholinduced impairment of the skills necessary to drive a vehicle safely (Deveaux, 1999;McLean et al, 1995). It is known that driving is made more difficult by alcohol-induced impairment of visual perception (Quintyn et al, 1999) and motor function (coordination, reaction delay, precision of movement, etc.) (Garriott, 1996;West et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Each of the tests have been widely employed as indices of a range of key cognitive processes that have previously been shown to be sensitive to the effects of alcohol intoxication, such as speed of information processing [10], [11], [12], [13], [14], [15], [16], divided attention [17], [18], [19], [20], [21], [22], [23]; problem solving [24], [25], [26], [27], [28], [29], [30], working memory [31], [32], [33], [34], [35], [36], response inhibition and cognitive flexibility [37], [38], [39], [40], [41], [42], and psychomotor functioning [18], [43], [44], [45], [46].…”
Section: Introductionmentioning
confidence: 99%